Determinants of ESG Reporting Difficulty in the Absence of Global Standardization - Buboi (Danailă), Angelica (Acta Universitatis Danubius. Œconomica, 2025)
In recent years, the increasing demand for transparent and comparable ESG (Environmental, Social and Governance) disclosures has placed considerable pressure on organizations worldwide to align with emerging sustainability standards. However, the absence of a globally standardized ESG reporting framework continues to generate significant challenges, especially in emerging economies such as Romania. This paper investigates the perceived difficulty of ESG reporting in the Romanian context by empirically testing the influence of key organizational factors using data collected through a structured questionnaire. Based on a sample of 291 respondents, the study employs an OLS econometric model to examine the effects of five core dimensions: the cost of data collection, information complexity, data reliability, report comparability, and the perceived influence of global regulations and ethical principles. The findings confirm that the perceived difficulty of ESG reporting is positively and significantly associated with high data collection costs, the complexity of ESG information, unreliable internal data systems, and the lack of inter-organizational comparability. In contrast, the influence of global regulations and ethics does not appear to be a significant determinant in the Romanian case. The results highlight the need for national policy frameworks to harmonize with European directives and to provide institutional support for developing digitalized, integrated ESG reporting systems. Furthermore, the paper suggests that increasing data reliability, reducing informational complexity, and strengthening organizational capacity are critical for facilitating effective ESG disclosure and avoiding structural underreporting in emerging markets.